ANALISIS KUALITAS PELAYANAN PADA BOLLY DEPT STORE TENTE - Lia Elisa; Herry Nurdin (Jurnal Ilmiah Satyagraha, 2021)
Satisfying consumer needs is the dream of every company. Apart from being an important factor for the survival of the company, meeting consumer needs can increase its superiority in the competition. Consumers who are satisfied with service quality tend to repurchase the product and reuse the product when the same need reappears in the future. This study aims to determine the analysis of service quality at the bolly department store tente. This research uses a quantitative approach with a survey method, while this type of research includes descriptive research. The population in this study were consumers who had used jt services, the number of samples taken in this study were 96 respondents. The research instrument used a questionnaire with a Likert scale. The data analysis used was validity test, reliability test, statistical analysis test (One-Sample Statistics, One-Sample Test). To test the effect between variables using SPSS (Statistical Service Product Solutions) version 23.00. Based on the results of the one-sample t-test at the bolly department store tente, it is said to be good because it meets the criteria of 50%, which means that the quality of service at the bolly department store tente is in accordance with the wishes of consumers.